Fiscal policy in a decentralized space of the financial system of Ukraine - Trusova, Natalia; Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Synchak, Viktor; Borovik, Liubov; Kostornoi, Serhii; Косторной, Сергій Володимирович; Косторной, Сергей Владимирович; Chkan, Iryna; Чкан, Ірина Олександрівна; Чкан, Ирина Александровна; Forkun, Iryna (Lifescience Global, 2020)
The article deals with fiscal policy in the decentralized space of the financial system of Ukraine. The methodology of complex, systematic assessment of fiscal policy in the decentralized space of the financial system of the state is grounded. It is proved that effective methodological approach to assessing fiscal policy in the decentralized space of the financial system of the state is a vector auto regression (VAR), which provides dynamic correlation of time series with simultaneous determination of each exogenous and endogenous variable in the system, in case of fiscal impulses (shocks) in economy. The production-institutional function is used which, when adapting to the relationship between GDP and tax burden with specific statistics, changes the type of trend of tax revenue. A method for evaluating the effectiveness of financing targeted programs for decentralized territory has been developed. The dynamics of direct and indirect taxes to the state and local budgets are analyzed and the fiscal significance of VAT in GDP, the state budget and tax revenues of Ukraine is determined. The amount of tax debt and the state budget deficit has been estimated and the structure of tax benefits in terms of taxes and fees in Ukraine is presented. The projected values of real tax revenues per capita are substantiated and the forecast parameters of the level of subsidization of local budgets of decentralized territories are given.
Keywords: fiscal policy; tax revenues; value added tax; state budget; decentralized territory